Modifikasi Faktor Konversi Format dan Faktor Normalisasi Reliabilitas dalam Standar ASTM D 5457 untuk Penyempurnaan Standar SNI 7973:2013 (Modification of Format Conversion Factor and Reliability Normalization Factor in the ASTM D 5457 Standard Applicable for SNI 7973:2013 Standard) - Leonard D D Liliefna; Naresworo Nugroho; Lina Karlinasari; Sucahyo Sadiyo (Jurnal Ilmu dan Teknologi Kayu Tropis, 2019)
The Indonesian SNI 7973:2013 standard for wood design specification was an adopted standard from the USA national design specification (NDS) 2012. However, due to the climate differences between USA and Indonesia, the SNI 7973:2013 standard should be further modified in order to meet the climate condition in Indonesia. Format conversion factor (KF) and reliability normalization factor (KR) specified in the ASTM D 5457 standard contained the snow load for the duration of load factor. Therefore, the objectives of this study were (1) to replace snow load with occupancy live load to revise KF, (2) to use the revised KF and safety factors for softwood and hardwood to perform the reliability analysis on calculated resistance factors (fc), (3) calculate the new KR values using the revised fc. The result of FORM reliability analysis showed that there were, on the average, 15 and 26% increases of the calculated KR values, respectively, for softwood and hardwood, over the calculated KR values according to the ASTM D 5457 standard for each given coefficient of variation of material resistance distribution.